ЗАПОЗИЧЕННЯ З АНГЛІЙСЬКОЇ МОВИ В УКРАЇНСЬКИХ СЛОВНИКАХ ІНШОМОВНОЇ ЛЕКСИКИ - Ткач, Людмила Олександрівна; Сулима, Софія Петрівна (Видавництво Національного університету «Острозька академія», 2020)
Anglicisms, a separate group of borrowed vocabulary, are recorded in the registers of Ukrainian dictionaries of foreign vocabulary from the beginning of the twentieth century, when the first scientifically developed dictionary of this type was published – “Dictionary of foreign words” by Z. Kuzelia and M. Tchaikovskyi (1910, Chernivtsi). The Anglicisms and untranslatable words, phrases, phraseological inversions of the English language represented in it, are thematically correlated with the following spheres: socio-political life and social movements; machinery and industry; sports and leisure; economics and finance; human life; urban locations, etc. In the dictionaries of this type, published in the twentieth century, both inside and outside Ukraine (thanks to the efforts of representatives of the Ukrainian diaspora), a number of changes can be observed in the lexicographic description of Anglicisms: 1) the number of words; 2) spelling; 3) interpretation of semantic structure of the vocabulary, ideological connotations; 4)derivation links, etc.
BORROWINGS FROM ENGLISH LANGUAGE IN UKRAINIAN DICTIONARIES OF FOREIGN VOCABULARY
Keywords: українська лексикографія ХХ ст.; англізми в українській літературній мові; „Словар чужих слів” З. Кузелі і М.Чайковського (1910); „Словник чужомовних слів” (1932; 1955); „Словник іншомовних слів” за ред. О. С. Мельничука (1974, 1985)